Inside the currency market : mechanics, valuation, and strategies - Twomey, Brian, 1961- (Bloomberg financial series., 2012)
"A complete resource to trading today's currency market. Currency movements are impacted by a variety of factors, including interest rates, trade balances, inflation levels, monetary and fiscal policies, and the political climate. Traders use both fundamental data and a variety of technical tools to trade within this market. Inside the Currency Market describes both the underlying dynamics that drive this market and the strategies that can help you capture consistent profits in it. Page by page, this reliable guide skillfully discusses the structure of the market, its roles in the global economy, the forces that drive currency values, trading strategies, and tactics. It also offers a detailed understanding of how global financial flows, derivatives, and other markets such as oil and gold impact currencies. Along the way, author and professor Brian Twomey provides information on gathering and analyzing global financial data so that traders can gain a "big-picture" perspective when attempting to identify trades.Explains virtually every element of the market and can function as a desk reference that puts everyday events into context for tradersFundamentally driven trades based on interest rate differentials and trade imbalances are discussed, as well as technical trades involving chart patterns, trends, and trading ranges Each chapter contains questions and answers to help readers master the material The currency market continues to generate interest and attract new retail traders due to the many opportunities available within it. This book will show you how to successfully operate within this arena by making the most informed trading decisions possible"--